Penyuluhan Pentingnya Sertifikasi HKI pada Industri UMKM di RW 04 Kelurahan Pondok Rajeg, Kecamatan Cibinong, Kabupaten Bogor - Rachmat Arnanda; Saidatuningtyas, Ifa; Ardhan, Dhea Tisane; Khoirunnisa, Ratna (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
This community service program aims to enhance the understanding and awareness of Micro, Small, and Medium Enterprises (MSMEs) regarding the importance of Intellectual Property Rights (IPR) certification as a form of legal protection and a means to improve business competitiveness. The activity was conducted in RW 04, Pondok Rajeg Village, Cibinong District, Bogor Regency, targeting local MSME actors. The program employed a Community Based Research (CBR) approach, emphasizing active community participation through problem analysis, target assessment, program development, and implementation stages. The main activity consisted of counseling sessions covering the concept of IPR, types of IPR, benefits of ownership, and online registration procedures through the Directorate General of Intellectual Property (DGIP). Evaluation was carried out using pre- and post-activity questionnaires. The results indicate that although all participants recognized the importance of IPR protection, their initial level of understanding was relatively low. Following the counseling session, there was a significant improvement in participants’ knowledge of IPR types and registration procedures. This program is expected to encourage MSMEs to register their intellectual property to protect innovation and enhance sustainable business competitiveness.